Simulasi Pijat Oksitosin dan Breast Care terhadap Produksi ASI pada Ibu Masa Nifas - Nurul Faizin; Andi Mustika Fadillah; Ummul Khair; Indah. S. P. Lumeno; Reli Sipata; Sry Wahyuni (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2025)
Breast milk (ASI) is the primary and natural food for newborns, providing the necessary energy and nutrients from birth to six months of life, promoting optimal growth and development. However, according to information obtained, about 30% of mothers face challenges in breastfeeding, particularly during the first few days after delivery. To address this issue, interventions such as breast care and oxytocin massage can stimulate breast milk production and prevent issues like mastitis. Oxytocin massage helps stimulate the milk ejection reflex, while breast care ensures the cleanliness of the breasts, making it easier for the baby to latch. The aim of this community service activity is to enhance mothers' knowledge through an educational program focused on oxytocin massage and breast care to improve milk production in postpartum mothers. The method used for this activity is an interactive educational session using tools like PowerPoint and leaflets, followed by a Q&A session and discussion. The evaluation was conducted through oral questioning, as well as by observing participants' enthusiasm during the session. The expected outcome of this activity is to provide mothers with practical knowledge and skills on breast care and stimulating breast milk production, ultimately supporting successful exclusive breastfeeding.